Financial distress determinant analysis of SMES on the Indonesia stock exchange / Ossi Ferli, Muhammad Zaki Alfarrel, Annisa Nabila Yasmin and Nadiya - Ferli, Ossi; Alfarrel, Muhammad Zaki; Yasmin, Annisa Nabila Yasmin; -, Nadiya (UiTM Cawangan Johor, 2023)
National movement of class increases for SNfEs since 2017 in Indonesia, where SNfEs can start to be listed in the Indonesian capital market showing data that has increased in number every year and increased contribution to Indonesia's GDP. The study aims to analyze the influence of internal corporate and macroeconomic variables on financial distress. This quantitative research used sixteen SMEs on the IDX selected using purposive sampling during the period 2017 - 2020. Data processing uses logistic regression with SPSS applications. The results showed that operating income to total assets showed a negative and significant influence between operating income to total assets and the occurrence of financial distress in SD'Æs listed on the IDX. The study was conducted by adding macroeconomic variables to fill the literature gap from previous studies. However, macroeconomic variables did not have a significant influence on the financial distress of SNfEs on the IDX To avoid financial distress, SMEs can make efficiencies on costs to increase operating income and maintain their level of liquidity stability, leverage, and managerial capabilities in line with the increasing assets of the company. Keywords: Financial Distress, Internal Corporate Factor, Logistic Regression, Macroeconomic Factor, SMEs